Pharmacokinetic and pharmacodynamic evaluation of a single dose of new, first in world, high dose aqueous formulation versus conventional oil based preparation of cholecalciferol - Changani, Mohit; Soni, Ameet; Chatterjee, Arani; Amarsheda, Ashish; Mavadhiya, Chandrakant (International Journal of Research in Medical Sciences, 2023)
Background: Vitamin D deficiency (VDD) is a common condition in India with prevalence in general population varying from 50-94%. VDD has been associated with increased susceptibility to a wide range of viral infections including COVID-19. It is associated with worse outcomes and greater morbidity and mortality in medical as well as surgical ICUs. The objective of the study was to evaluate the pharmacokinetic (PK)/pharmacodynamic (PD) of aqueous cholecalciferol injection in comparison with conventional oil-based injection in VDD healthy adult subjects. Methods: 24 eligible vitamin D deficient healthy adult males, fulfilling the inclusion/exclusion criteria, were enrolled in the study. Subjects received a single dose of either test (T) [Aqueous cholecalciferol injection 600K IU/2 mL] or reference (R) [Cholecalciferol 600K IU oil-based injection] intramuscularly. Various PK parameters (Cmax, AUC0-t, AUC0-∞ and Tmax) and PD parameters (concentration of cholecalciferol and 25(OH)D) were measured along with safety analysis. Results: A significantly higher concentration of cholecalciferol and 25(OH)D were observed with test product compared to reference (p<0.01) from 1-hour post-administration till end of the study. A statistically significant difference between test and reference product was observed for the calculated Cmax and Tmax for cholecalciferol and 25(OH)D (p<0.0001). All 12 (100%) subject in test arm achieved the normal level of 25(OH)D by 72 hr post-administration as compared to none in reference arm (p=0.0017). There were no serious adverse events (SAEs) or deaths reported during the study. Conclusions: This first in world, aqueous formulation of cholecalciferol injection was found to be superior in various PK/PD parameters as compared to conventional oil based injection, which resulted in rapid and sustained rise in serum 25(OH)D levels.